Presentation of sinonasal carcinoma (Bangladesh Journal of Otorhinolaryngology, 2014)
Objective: To observe the pattern of clinical presentation according to site of origin of sinonasal carcinoma. Methods: This cross-sectional study was done in the Department of Otolaryngology-Head and Neck Surgery, BSMMU and Dhaka Medical College Hospital, Dhaka during the period from January 2008 to December 2009. Patients of sinonasal carcinoma were evaluated by detailed history, clinical examination and relevant investigations. Results: The present study included 40 patients of sinonasal malignancy bearing age limits of 4 years to 75 years with mean age 48.29. Male and female ratio was 2.6:1. Most patients (77.5%) came from rural area and illiterate (40%) and most of them were farmers (40%), having poor socio-economic condition (50%). About 35% of them were smokers and more than one other personal habit. Majority patients presented with multiple sinuses involvements (72.5%) and among single sinus involvement maxillary sinus was most common (63.63%), followed by nasal cavity (27.27%) and ethmoidal sinus (9.09%) as primary site. Conclusion: Though carcinoma of the nose and paranasal sinuses is relatively uncommon, it is not uncommon in our country. This disease generally presents in an advanced stage. Overall prognosis was directly related to diseases stages. DOI: http://dx.doi.org/10.3329/bjo.v19i2.17632 Bangladesh J Otorhinolaryngol 2013; 19(2): 99-103